Effect of seedling number per hill and seedling age on plant growth and grain yield Ciherang Rice - Yenni Asbur (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Rice (Oryza sativa L.) is an important plant as one of the main food sources in Indonesia. Efforts to increase the productivity of rice conducted with intensification, by intensifying the use of seedling number per hill and seedling age while transplanting. The research were conducted to determine the effects of seedling number per hill and seedling age on plant growth, and grain yield Ciherang rice. The research was done at UPT. Balai Benih Induk (BBI) Perdamean village Tanjung Morawa from March 2012 to June 2012. Reducing seedling number per hill from 5 to 3 and 1 respectively, increased plant growth and grain yield significantly. Increasing seedling age from 7 to 14 and 21 days resulted in significant increasing plant growth and grain yield. In general, transplanting 7-21 day-old seedlings at one seedling per hill increased plant growth and grain yield Ciherang rice